RELATIONSHIP OF ULTRASOUND MEASUREMENTS AND CARCASS TRAITS IN PELIBUEY EWES - E. Aguilar-Hernandez; A. J. Chay-Canul; A. Gomez-Vazquez; J. G. Magaña-Monforte; F. G. Ríos-Rincón; A. Cruz-Hernandez (Journal of Animal and Plant Sciences, 2016)
Twenty Pelibuey ewes were used to assess the relationship between ultrasound measurements (USM) and carcass traits. Animals were slaughtered, and the left half of each carcass was divided into five cuts, and then each cut was dissected into muscle, fat and bone. The subcutaneous fat thickness and the Longissimus dorsi muscle area were determined 24 h pre-mortem using a ultrasound equipment, the USM were taken between the 12ª and 13ª thoracic vertebra (TF and TLD) and between 3ª and 4ª lumbar vertebra (LF and LLD). The relationships among USM and carcass traits were estimated by regression. The regression equations using only the USM have a R2 that ranged from 0.22 to 0.45. When including the BW in the equations, the R2 was from 0.52 to 0.55 for muscle, 0.51 to 0.53 for fat and 0.47 for bone. The best equations were: CM (kg) = 0.18(±0.03)×BW +0.38(±0.17)×TLDA; CF (kg)= -1.66(±0.79*)+ 0.09(±0.03**)×BW + 0.38(±0.19*)×TFT -0.11(±0.09ns)×TLDA and CB (kg)= 2.44(±0.49)***+ 0.06(±0.01***)×BW+ -0.23(±0.11*)×TFT. In conclusion, it is possible to predict the amount of muscle, fat and bone in the carcasses of adult Pelibuey ewes using USM and BW, nonetheless, other alternatives, should be considered to improve the accuracy of predictions.
Keywords: Pelibuey ewes; carcass composition; ultrasound measurements